Impact of Domestic Public Debt on Economic Growth - An Empirical Study in the Indian Context - Gangadharan, Srinivasa Rao; Padmakumari, Lakshmi (Asian Journal of Empirical Research, 2016)
This study is an empirical investigation to assess the impact of domestic debt on India’s Economic growth during the period 1980 – 2014. We use data on Domestic Debt, Net Fiscal Deficit, Exports, Savings, Real Gross Domestic Product, Population and Terms of Trade. This study adopts the ARDL Co-Integration and Granger Causality techniques to investigate the relation between the key variables. The study also employs various post estimation tests to validate the fitness and stability of the models based on Gauss Markov assumptions, after employing the ordinary least square regression on various models. We find that debt negatively impacts economic growth while savings has a positive impact. The Auto Regressive Distributed Lag (ARDL) technique used to test the robustness suggests existence of co-integration among the variables. However, none of the long run co-efficient is significant. The granger causality and co-integration test results support the traditional view that debt negatively impacts economic growth.